Pemilihan Batu Bata Menggunakan Metode Simple Additive Weighting (SAW) - Nanda, Thoyib Fernanda; Daniati, Erna; Ristyawan, Aidina (Nusantara of Engineering (NOE), 2023)
This study focuses on the selection of bricks based on criteria. Many types of bricks have been marketed, but the many criteria and lack of knowledge and information about the types of bricks makes it difficult for customers to choose bricks. One alternative solution to solve this problem is to use a decision support system using the SAW method to make it easier for customers to make decisions about choosing bricks according to their wishes. The SAW method is used to determine the highest score from the ranking results, there are existing alternatives by calculating the predetermined criteria and weights. by using an application that can be updated according to customer needs. The results of implementing a Decision Support System using the SAW method help customers make decisions about choosing bricks more easily.